Preparation and spectroscopic properties of Ca2Al2SiO7: Tb3+ phosphor - Tien, Do Thanh; Son, Nguyen Manh (Hue University Journal of Science: Natural Science, 2019)
The Tb3+ rare earth ion doped Ca2Al2SiO7 material has tetragonal phase structure that has been successfully synthesized by solid state reaction method with optimal conditions: the sintering temperature at 1280oC for duration of 60 minutes and the B2O3 flux agent content 4%wt. The Photoluminescence (PL) spectrum of Tb3+ doped Ca2Al2SiO7 phosphor consists of narrow lines with peaks at 545 nm, 440 nm, 462 nm, 494 nm, 590 nm and 622 nm that corresponding to 4f electronic transitions of Tb3+ ion. The peak at 545 nm has the highest luminescent intensity. The influence of synthesis technology and the luminescent characteristics of the phosphor are presented and discussed.